1997
DOI: 10.1016/s0305-750x(96)00138-6
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder dairying under transactions costs in East Africa

Abstract: A subsequent draft has benefitted tremendously from the insightful comments of Marcel Fafchamps, Barbara Grosh, Bruce Johnston and William Steel. Remaining errors are the responsibility of the authors. ii It is argued that dairying is vital to future viability of many small farms in East Africa and that high transactions costs for dairy production and marketing limit participation by asset-and information-poor smallholders. Case studies from Kenya and Ethiopia illustrate the role of dairy cooperatives in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 5 publications
3
121
1
6
Order By: Relevance
“…Generally, it would be expected that the more producers become concerned about meeting buyers' quality requirements, the less of mushrooms they will supply to that particular channel. However, as observed by Staal et al (1997), it could be inferred that while producers were often uncertain about whether their mushrooms would meet the buyers' expectations for quality, the market reliability and comparatively better exchange price offered by the retail market seemed to outweigh the uncertainty about quality such that producers were willing to increase their supply in order to avoid the farm gate option, which relies mostly on unpredictable consumer turnout. …”
Section: Factors Affecting Channel Choice and Quantity Suppliedmentioning
confidence: 99%
“…Generally, it would be expected that the more producers become concerned about meeting buyers' quality requirements, the less of mushrooms they will supply to that particular channel. However, as observed by Staal et al (1997), it could be inferred that while producers were often uncertain about whether their mushrooms would meet the buyers' expectations for quality, the market reliability and comparatively better exchange price offered by the retail market seemed to outweigh the uncertainty about quality such that producers were willing to increase their supply in order to avoid the farm gate option, which relies mostly on unpredictable consumer turnout. …”
Section: Factors Affecting Channel Choice and Quantity Suppliedmentioning
confidence: 99%
“…Several studies have shown that market participation by resource-poor smallholders is hindered by high transaction costs (Staal et al 1997;Holloway et al 2000). Implementation of the revised Kenya dairy policy reduced transaction costs and hence, marketing margins.…”
Section: (A) Policy Impact On Transaction Costs: a Model Of Equilibrimentioning
confidence: 99%
“…Examples of these studies are Staal et al (1997), Frank & Henderson (1992), Key, Sadoulet & de Janvry (2000), Hobbs (1997) andLoader (1997). Very few empirical studies have actually measured transaction costs to-date, probably due to the difficulties associated with their measurement.…”
Section: Transaction Cost Economics In Agricultural Policy Researchmentioning
confidence: 99%